iMEC-APCOMS 2017 - Taking the Factories to the Next Level - Siti Sarah, Mohamad Rajimi (2018)
Yogyakarta, 7 Disember - Nearly 100 participants from local and abroad get together for International Manufacturing Engineering Conference – Asia Pacific Conference on Manufacturing Systems (iMEC-APCOMS) 2017. This year, the main theme address about “Taking the Factories to the Next Level.”